If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4g + 3(-7 + 2g) = 1 + -1g 4g + (-7 * 3 + 2g * 3) = 1 + -1g 4g + (-21 + 6g) = 1 + -1g Reorder the terms: -21 + 4g + 6g = 1 + -1g Combine like terms: 4g + 6g = 10g -21 + 10g = 1 + -1g Solving -21 + 10g = 1 + -1g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'g' to each side of the equation. -21 + 10g + g = 1 + -1g + g Combine like terms: 10g + g = 11g -21 + 11g = 1 + -1g + g Combine like terms: -1g + g = 0 -21 + 11g = 1 + 0 -21 + 11g = 1 Add '21' to each side of the equation. -21 + 21 + 11g = 1 + 21 Combine like terms: -21 + 21 = 0 0 + 11g = 1 + 21 11g = 1 + 21 Combine like terms: 1 + 21 = 22 11g = 22 Divide each side by '11'. g = 2 Simplifying g = 2
| 14-7x=174-42x | | 2g+4(-6+2g)=1-g | | 36x=x*(r*r) | | 6x-91=3x-2 | | t^2-2t-36=0 | | -6g-4=-3g+2 | | 3x-4=4x-2 | | 3x-4=4x-ray | | -8=-2a+6 | | x^3-7x= | | 3x+29=11x-43 | | -6m+69-9(m-1)=4m-(2m-2)-7m+6 | | 10y^2-19y+6=0 | | 6p-8=8-30p | | 93=9*(e^2x) | | 2x+8=64-4x | | -3r+7=5r-3 | | 5.2y+7.2=30.6-1.3y | | 4b-21=28 | | y=4-3*2 | | 104-7x=29x+24 | | 0.47x=-3.23x+62.9 | | 93=9e^2x | | 7=9x-1 | | c+0.1c+0.01c-0.001c=c+0.545 | | 36-6x=18+3x | | n^2+n-400=0 | | 3(r-3)-r=-4(2r+5)-8 | | 3(s+4)+2s=67 | | 6=9x-7 | | c+0.1c+0.01c-0.001c=c | | 2=13g-77 |